Culture-led urban regeneration / edited by Ronan Paddison and Steven Miles. - Paddison, Ronan; Miles, Steven (Routledge, 2007)
'Culture-Led Urban Regeneration' focuses on the ability of cultural investment to meet the rhetoric of social inclusion, and the extent to which it offers sustainable solutions to the problems of the city.